Dental iron precipitates in patients with Type 2 diabetes - Ortiz Arrambide, Miguel Ángel; Juarez Ibarra, Karla Isabel; Malagón Santiago, Guadalupe Ismael; Cruz Fierro, Norma; De la Garza Ramos, Myriam Angélica (2018)
Diabetes mellitus (DM) is a frequent worldwide disease. There are currently more than 46 million people who suffer this disease in North America and the Caribbean. The objective of this study was to determine if there is an association between DM and the presence of iron precipitates (Fe2+) in dental structure. The third molar was extracted for reasons that merit extraction from 40 individuals with and without DM to analyze dentin tissue. Horizontal and longitudinal slices of tooth samples were made and later stained with 10% potassium cyanoferrate. The samples were observed by optical microscope to identify basophilic elements. A nonparametric Spearman correlation was performed to find an association between the quantitative (gender, group, and dentinal tissue) and qualitative variables (gender). The Mann–Whitney U test was used to find differences in the means of the nonparametric variables in two different groups in relation to the P value (<0.05). Iron elements were found in the predentin and circumpulpal dentin areas, and the results obtained showed a statistically significant difference between dentin tissue from patients with diabetes and those without. Individuals with Type 2 DM are prone to present iron precipitates in predentin and circumpulpal dentin tissue. Few iron elements were found in dental organs of individuals without DM.